Shedding of infectious Borna disease virus-1 in living bicolored white-toothed shrews - Nobach, Daniel; Bourg, Manon; Herzog, Sibylle; Lange-Herbst, Hildburg; Encarnação, Jorge A.; Eickmann, Markus; Herden, Christiane; Justus Liebig University Giessen (My University, 2015)
Background:Many RNA viruses arise from animal reservoirs, namely bats, rodents and insectivores but mechanisms of virus maintenance and transmission still need to be addressed. The bicolored white-toothed shrew (Crocidura leucodon) has recently been identified as reservoir of the neurotropic Borna disease virus 1 (BoDV-1) Principal Findings: Six out of eleven wild living bicoloured white-toothed shrews were trapped and revealed to be naturally infected with BoDV-1. All shrews were monitored in captivity in a long-term study over a time period up to 600 days that differed between the individual shrews. Interestingly, all six animals showed an asymptomatic course of infection despite virus shedding via various routes indicating a highly adapted host-pathogen interaction. Infectious virus and viral RNA were demonstrated in saliva, urine, skin swabs, lacrimal fluid and faeces, both during the first 8 weeks of the investigation period and for long time shedding after more than 250 days in captivity. Conclusions: The various ways of shedding ensure successful virus maintenance in the reservoir population but also transmission to accidental hosts such as horses and sheep. Naturally BoDV-1-infected living shrews serve as excellent tool to unravel host and pathogen factors responsible for persistent viral co-existence in reservoir species while maintaining their physiological integrity despite high viral load in many organ systems.
Keywords: ddc:630